Due To Legal Marriage Without Married Agreement Relating To The Existence Of Bankruptcy - Reza Fahlevi Bachtiar; Umar Ma'ruf (Jurnal Akta, 2018)
The problems that will be answered in this study are grouped into two, about how the legal consequences of marriage, held without mating agreement with the bankruptcy, and how the legal standing of the assets of the debtor spouse to mate without mating agreement after bankruptcy. The method used in this research is the empirical jurisdiction. The legal consequences of marriage, held without mating with their bankruptcy agreement is legally valid as the bankruptcy of the husband or wife of the bankrupt debtor. The separation between the property along with a personal wealth does not necessarily separate due to the bankruptcy imposed on married couples who enter into marriage without mating agreement as well as the marriage held by mating or separation agreement treasure. The legal position of property the debtor spouse into marriage without the agreement having been declared bankruptcy mating separated into two parts, namely the unity property and personal possessions. Husband or wife treasure the bankruptcy debtor entered into treasure union declared legally bankrupt as a result of participating bankruptcy imposed against the partner.Keywords: Effects; Marriage; Marriage Agreement; Bankruptcy.